Molecular Screening and Production of α-amylase from Fungal sp. - Agwu, Cletus H. (European Journal of Applied Sciences, 2021)
α-amylase producing Aspergillus sp. was isolated from decaying bread collected from bakery site located within Enugu metropolis, Enugu state. Standard microbiology, biochemical and molecular techniques (18s DNA sequencing) were used for confirmation of the fungal strain as Aspergillus tamari.. p-NPG infused nutrient broth confirmed Aspergillus tamarrii as prolific producer of α-amylase with rapid yellow colouration after forty eight hours of incubation. Solid state fermentation on rice bran matrix (SSF) system was used for the enzyme production. Cork borer of 2mm diameter was used throughout the production and optimization studies. Carbon sources including: Starch, wheatbran and sugarcane baggase were optimized, starch was found suitable for the protein production with highest α-amylase activity (91.71 μmol/min). Among the nitrogen sources optimized, peptone was found optimal for α-amylase production with activity of 90.34 μmol/min. pH 6.0 was found the best for the enzyme production. Effect of incubation period on the enzyme production showed the 4th day of fermentation as the peak day for α-amylase production from Aspergillus tamari. The results from this study have shown that Aspergillus tamari among other fungal isolates from mould bread collected from bakery sites in Enugu metropolis has the potential for α-amylase production in a commercial scale for both industrial and clinical applications..